Review of the slaughter wastes and the meat by-products recycling opportunities - Alibekov, Ravshanbek S.; Alibekova, Zaripa I.; Bakhtybekova, Asem R.; Taip, Farah S.; Urazbayeva, Klara A.; Kobzhasarova, Ziba I. (Frontiers in Sustainable Food Systems, 2024)
In the ancient times, the Kazakhstan population were considered as nomadic people, where a cult of all types of cattle breeding had a leading position. However, currently the processing approaches of livestock slaughter wastes and secondary meat raw materials are weakly developed. The presented review of waste-free technologies considers the utilization processes of following: carcasses, skins, bones, meat scraps, blood, adipose tissue, horns, feet, hooves, and internal organs. These substances are an important source of animal protein, collagen, bioactive peptides, blood plasma, minerals, and fats that can be applied in various industries: food, feed, medical, and technological. When slaughtering livestock, meat on bones makes up almost half of the total weight of livestock, yet the remaining half contains offal and inedible raw materials. Blood consists of: erythrocytes, leukocytes, platelets, and plasma. Animal bones have mostly proteins (30–50%) and lipids (13–20%) from bone tissues. Tendons, bones and skins contain a large amount of collagen. Animal fat and adipose tissue have 54.9% saturated acids, 40.9% unsaturated fatty acids and 4.2% polyunsaturated fatty acids. Bioactive peptides from collagen derivatives contain from 2 to 20 amino acids and have various biological (antihypertensive, antioxidant, and antimicrobial) activity. This review considers a world current status, modern prospects and opportunities in the slaughter wastes and the meat by-products recycling technologies. Overview of existing approaches for waste processing with the subsequent use of the final product in the food industry, the production of feed, medicines and technical products is considered. The complete processing within the slaughtering livestock and the secondary meat raw materials allows to expand the wide-range products with a low prime cost, thereby promoting to the sustainable development of agroecology by applying the waste hierarchy: Reducing, Reusing, and Recycling.